Stage and mortality of low‐income patients with cancer: Evidence from SEER‐Medicaid. Issue 2 (27th October 2020) - Bradley, Cathy J.; Stevens, Jennifer L.; Enewold, Lindsey; Warren, Joan L.
Abstract : Background: A national data source for identifying patients with cancer enrolled in Medicaid is needed to evaluate cancer care for low‐income, publicly insured patients. In this study, a population‐based data set of patients diagnosed with cancer and enrolled in Medicaid was created and evaluated. The objective was to compare the characteristics of patients with cancer identified in Surveillance, Epidemiology, and End Results (SEER) data and linked to the Medicaid Analytic eXtract (MAX) Personal Summary files with the characteristics of patients who were not linked to the MAX file. Methods: All persons in 14 SEER registries diagnosed with cancer from 2006 to 2013 who were or were not linked to the 2006‐2013 nationwide MAX files were selected, and patient demographic characteristics were compared for 3 age groups. Common cancer sites and the timing of Medicaid enrollment with respect to patients' cancer diagnoses were reported, and the stage at diagnosis and 4‐year mortality were compared by 3 categories of Medicaid enrollment. Results: Approximately 18% of the sample was enrolled in Medicaid within 25 months of diagnosis. Enrollees had a greater proportion of racial/ethnic minorities in comparison with patients who were not enrolled. A late‐stage diagnosis was more common among Medicaid patients and particularly among those who enrolled after their diagnosis. For every common cancer site, mortality was highest in the sample of Medicaid patients who enrolled after their diagnosis. Conclusions: The Medicaid enrollment data newly added to SEER records enhance researchers' ability to investigate research questions related to Medicaid policies and care delivery. For patients enrolled before their diagnosis, Medicaid appears to offer protection against late‐stage disease and mortality. Abstract : A national data source for identifying patients with cancer who are enrolled in Medicaid is needed to evaluate cancer care among low‐income, publicly insured patients. For patients enrolled before their diagnosis, Medicaid appears to offer protection against late‐stage disease and mortality.